Spectrophotometric Determination of Hydrogen Peroxide Based on Fading of Tribromoarsenazo Oxidation by Hydrogen Peroxide Catalyzed by Hemoglobin - Zhai, Qing-Zhou; Zhang, Xiao-Xia; Zhang, Rui-Bo (Asian Journal of Chemistry, 2013)
In pH 3.2 CH3COOH-CH3COONa buffer solution, bovine hemoglobin (Hb) catalyzes the decolouring of oxidation tribromoarsenazo (TB-ASA) by hydrogen peroxide and between fading degree DA and H2O2 concentration a linear relationship exists. Based on this principle, a novel method for the determination of H2O2 has been developed. The results showed that the maximum absorption wavelength of the system is 400 nm. At this wavelength, the apparent molar absorptivity of the method is e400 nm = 1.01 × 103 L·mol-1·cm-1 and the linear range is 4.0 × 10-5-3.4 × 10-4 mol L-1 with a detection limit of 2.1 × 10-5 mol L-1. The present method has been successfully applied to the determination of H2O2 in rain waters.